Employee Perspective Analysis on Optimizing Insurance Use in Occupational Safety and Health Programs - Ashaari, Taslam; Syahriza, Rahmi; Kusmilawaty, Kusmilawaty (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This study aims to analyze employees' perspectives on the optimization of insurance use in occupational safety and health programs at PT Kereta Api Logistik. Insurance is an important instrument in providing financial protection against the risk of work accidents and occupational diseases in a logistics company environment that has a high level of risk. This study uses a qualitative approach, with data collection using in-depth interviews with 8-12 employees involved in the occupational safety and health insurance program. Data collection techniques also include direct observation and the study of relevant documentation and documents. The results show that most employees feel protected and satisfied with the insurance benefits, especially in terms of medical expenses and work accident compensation. However, insurance coverage is not comprehensive, and the claims process is still not transparent and slow. A lack of education about the claims procedure was also found. The study emphasizes the importance of integrating insurance protection with training and strengthening the safety culture. Recommendations include expanding insurance coverage, digitizing claims, improving employee education, and collaborating with competent insurance providers. With these steps, the optimization of insurance protection is expected to support the optimal success of the Occupational Safety and Health program at PT Kereta Api Logistik.